Les interactions asymétriques en famille: analyse qualitative du conflit verbal dans les conversations à table - Arcidiacono, Francesco (My University, 2008)
This work studies the verbal conflict between parents and preadolescents, through the analysis of family interactions at dinnertime. The aim of the research is to analyze the participants? strategies in situation of conflict and to highlight the relations between parents and preadolescents in these specific situations. The data collection methodology is mainly ethnographical: videotape recordings of Italian middle class family dinners were transcribed and codified following the approach of Conversation Analysis. The results of the qualitative analysis confirm the importance of the verbal conflict in family context as a particular cultural strategy of relationships between parents and preadolescents. The data also underline the relations between different aspects of conflict and their pragmatic implications for all family members at dinnertime conversations.
Keywords: famille; conflit en famille; adolescence